The sensitivity of the urban environment to natural hazards using the method of hierarchical analysis and geographic information system: the risk of floods in the city of Oued El Athmania as a model - sandra, Docteur, Boussetti (The journal of contemporary issues in business and government, 2023)
Natural phenomena in all their forms are one of the dangers that threaten humanity, and perhaps the danger of floods is one of the most lethal of these dangers due to the material and human losses they cause, a threat that all countries of the world suffer from and have become a frequent occurrence in recent times. Algeria in general and the city of Oued El Athmania, in particular, are considered areas at risk of flooding constantly, due to heavy and sudden precipitation, leaving material and sometimes human losses that accelerate the impact of urban expansion processes at the expense of unorganized agricultural land on the banks of Oued El Athmania in the center of the city. This study aims to identify and map the areas at risk of flooding in the city of Oued el Athmania, five criteria were introduced: slope, distance to valleys, and distance to dam Hammam Garouz, residential density, and land use, which were determined based on relevant available references, using one of the effective methodological approaches Hierarchical Analysis (AHP). This method determines the final weight of each criterion affecting floods based on the opinions of local experts and decision-makers, and then conducts the weighted linear integration of the maps used in the GIS program, to obtain a map suitable for hazard sensitivity so that it can be used in decision- making towards planning flood management in the city of Oued El Athmania. The results of the case demonstrate that the GIS-AHP-based category model is effective in identifying flood risk areas; it confirms that the integration of AHP and GIS technologies provides a powerful tool for decision-making procedures in flood risk mapping, allowing for a coherent and efficient use of spatial data.